2018
DOI: 10.1182/blood-2017-09-746420
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and the management of hematologic malignancies

Abstract: The majority of blood cancers occur in the elderly. This fact conspires with an aging population in many countries to make rigorous assessment for frailty increasingly important for hematologic oncologists. In this review, we first define frailty and its relevance for patients with hematologic malignancy. Next, we review current data regarding the effect of domains of frailty on outcomes for blood cancers including myelodysplastic syndromes, acute leukemia, non-Hodgkin lymphomas such as chronic lymphocytic leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(79 citation statements)
references
References 74 publications
0
76
0
3
Order By: Relevance
“…This study provides additional information to support testing the role of GA to enhance risk prediction in the context of intensive AML therapy. Identifying characteristics of patients who are more or less likely to tolerate and benefit from intensive chemotherapy is critical for both treatment decision-making, trial design and supportive care [44]. A single institution study showed that physical performance and cognition (measured by the Short Physical Performance Battery and Modified Mental State Exam) are associated with worse survival among older adults treated intensively, but confirmatory multisite studies are lacking.…”
Section: Methodsmentioning
confidence: 99%
“…This study provides additional information to support testing the role of GA to enhance risk prediction in the context of intensive AML therapy. Identifying characteristics of patients who are more or less likely to tolerate and benefit from intensive chemotherapy is critical for both treatment decision-making, trial design and supportive care [44]. A single institution study showed that physical performance and cognition (measured by the Short Physical Performance Battery and Modified Mental State Exam) are associated with worse survival among older adults treated intensively, but confirmatory multisite studies are lacking.…”
Section: Methodsmentioning
confidence: 99%
“…For older, fit patients, intensive treatment with ASCT may be appropriate, while in the very frail, with GA and high R-MCIscores, end-of-life care discussions can be facilitated. 10,42 Concrete clinical designations of the use of the R-MCI 1. We have included the R-MCI in the weekly MM tumorboard, where this is being scored before the patient is discussed at an interdisciplinary level.…”
Section: Comparison Of the R-mci With Numerous Others [Cci Kaplan Fementioning
confidence: 99%
“…The clinical course of systemic lupus erythematosus (SLE) is variable and challenging to predict. In geriatric medicine and other disciplines , susceptibility to adverse outcomes is quantified using the construct of frailty, defined as increased vulnerability due to diminished ability to respond to physiologic stressors . One approach to operationalizing frailty is through a frailty index (FI) , which measures the accumulation of health deficits across multiple systems .…”
Section: Introductionmentioning
confidence: 99%